A small synthetic molecule functions as a chloride–bicarbonate dual-transporter and induces chloride secretion in cells. Issue 46 (18th May 2016) - Liu, Peng-Yun; Li, Shing-To; Shen, Fang-Fang; Ko, Wing-Hung; Yao, Xiao-Qiang; Yang, Dan
Abstract : A C 2 symmetric small molecule composed ofl -phenylalanine and isophthalamide was found to function as a Cl − /HCO3 − dual transporter and self-assemble into chloride channels. Abstract : A C 2 symmetric small molecule composed ofl -phenylalanine and isophthalamide was found to function as a Cl − /HCO3 − dual transporter and self-assemble into chloride channels. In Ussing-chamber based short-circuit current measurements, this molecule elicited chloride-dependent short-circuit current ( I sc ) increase in both Calu-3 cell and CFBE41o-cell (with F508del mutant CFTR) monolayers.